Improving Students' Literacy and Numeracy by Implementing Local Instructional Theory (LIT) - Ahmad Syah; Imran; Muhammad Assaibin (Global Journal Basic Education, 2026)
Low levels of student literacy and numeracy skills in resource-constrained schools present a fundamental challenge in basic education. This classroom action research aims to evaluate the improvement of 5th-grade students' literacy and numeracy competencies at MI DDI Tappina through the implementation of Local Instructional Theory (LIT). The study was conducted in two iterative cycles adapting the Kemmis & Taggart model, wherein a Hypothetical Learning Trajectory (HLT) was designed utilizing the local context and surrounding environment as the primary learning medium. Data were gathered through cognitive literacy-numeracy tests, student engagement observation sheets, and in-depth interviews. Findings indicate that the average student test score increased significantly from 53% in Cycle I to 79% in Cycle II, surpassing the classical mastery target (75%). This improvement aligns with student active engagement, which rose from 80% to 92%. Qualitative data revealed a positive shift in teacher and student responses, turning highly receptive and enthusiastic as instructional materials became more concrete and relatable. The core value of this study lies in demonstrating that Local Instructional Theory serves as an effective instructional framework to overcome facility and media limitations without relying on high-tech devices.